Peer support for stroke survivors: a case study - Kessler, Dorothy; Egan, Mary; Kubina, Lucy-Ann (Université d'Ottawa | University of Ottawa, 2014)
Innovative and sustainable programs are required to support the well-being of stroke survivors. Peer support is a potentially low cost way to enhance well-being of recent stroke survivors and the well-being and community reintegration of their peer supporters. This article describes the perceptions of stroke survivors, care partners, peer supporters, and professionals of an individual peer support program.
Keywords: Stroke; Social participation; Volunteers; Untrained workers; Caregivers